2022
DOI: 10.3390/ijms232416091
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Fucoxanthin through Cell Cycle Arrest, Apoptosis Induction, Angiogenesis Inhibition, and Autophagy Modulation

Abstract: Cancer accounts for one in seven deaths worldwide and is the second leading cause of death in the United States, after heart disease. One of the standard cancer treatments is chemotherapy which sometimes can lead to chemoresistance and treatment failure. Therefore, there is a great need for novel therapeutic approaches to treat these patients. Novel natural products have exhibited anticancer effects that may be beneficial in treating many kinds of cancer, having fewer side effects, low toxicity, and affordabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 218 publications
0
13
0
Order By: Relevance
“…In MDA-MB-468 cells, the FC for the significantly upregulated gene was EIF4EBP1 (+2. 16). The FCs for MDA-MB-468 downregulated genes were shown to be FOXO1 (−1.…”
Section: Fucoxanthin Modulation Of the Pi3k-akt Signaling Pathway In ...mentioning
confidence: 99%
“…In MDA-MB-468 cells, the FC for the significantly upregulated gene was EIF4EBP1 (+2. 16). The FCs for MDA-MB-468 downregulated genes were shown to be FOXO1 (−1.…”
Section: Fucoxanthin Modulation Of the Pi3k-akt Signaling Pathway In ...mentioning
confidence: 99%
“…19 After ingestion, Fucoxanthin is absorbed in the intestine, metabolized into Fucoxanthinol, and further transformed into Amarouciaxanthin A in the liver. 20,21 Accumulating evidence has revealed Fucoxanthin's diverse health-beneficial activities, including anti-angiogenic, anti-diabetic, anti-inflammatory anti-obesity, antioxidant, hepatoprotective, and anti-cancer 17,22,23 (and the references therein). Intriguingly, the precise impact of Fucoxanthin on human melanoma and its mechanisms of anti-melanoma action remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletonema marinoi ( Sm ), a temperate coastal marine diatom, has been recently proposed as a valid source of bioactive molecules. Diatoms contain several moieties of interest for human health, among them carotenoids, including fucoxanthin (Fuco) [ 11 , 28 , 30 , 31 , 32 , 33 ], diatoxanthin, and other pigments [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fuco represents the most abundant carotenoid contained in diatoms such as Sm and can be also isolated from brown seaweeds for human consumption [ 33 ]. Numerous studies have reported that Fuco has biological properties, acting as an anti-obesity, anti-diabetes, anti-oxidant, and anti-inflammatory molecule, and it also has cardiovascular and cerebrovascular protective effects [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation